Triple Convergence dan Masa Depan Perkembangan Manusia Indonesia: Pendidikan Farmasi, Kecerdasan Buatan, Pembatasan Media Sosial, dan Moralitas Anak Muda di Persimpangan yang Menentukan - Ilham Arief; Ardi Kho (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This article critically examines the convergence of three concurrent transformative forces in Indonesia: the development of pharmacy education, the acceleration of artificial intelligence (AI), and social media restrictions through Government Regulation No. 17/2025 (PP TUNAS) and Ministerial Regulation No. 9/2026, effective March 28, 2026. This revision integrates a fourth, previously overlooked variable: the influence of social media restrictions on the moral development of young people. Using the Triple Convergence analytical framework grounded in Sen's capability approach, Bronfenbrenner's developmental ecology, Vygotsky's ZPD theory, and Kohlberg's theory of moral development, this critical review synthesizes 83 sources (2020–2026). The findings reveal a structural paradox: the four forces have the potential to reinforce each other in producing clinically and ethically competent pharmacists, but also have the potential to be detrimental if not coordinated. Social media restrictions have the dual effect of protecting against harmful content while simultaneously reducing the space for developing empathy and moral reasoning, essential to the healthcare profession. This article argues that policies should be designed within an integrated framework centered on expanding human capabilities, including moral capabilities.